2013
DOI: 10.1016/j.future.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

An economic and energy-aware analysis of the viability of outsourcing cluster computing to a cloud

Abstract: ElsevierAlfonso Laguna, CD.; Caballer Fernández, M.; Alvarruiz Bermejo, F.; Moltó, G. (2013) AbstractThis paper compares the total cost of ownership of a physical cluster with the cost of a virtual Cloud-based cluster. For that purpose, cost models for both the physical cluster and the cluster on the Cloud have been developed. The model for the physical cluster takes into account previous works and incorporates a more detailed study of the costs related to energy consumption and the usage of energy saving str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 12 publications
0
18
0
1
Order By: Relevance
“…This paradigm can solve those disadvantages with customizable virtual machines (VMs) that decouple the application execution from the underlying hardware and are dynamically provisioned and released [1]. Because of that, depending on the resource usage and the cost model, it might be convenient to deploy a virtual cluster instead of a physical one, as we concluded in a previous work [2]. Virtual clusters in the Cloud introduce profound benefits for many computational workloads, but specially for embarrassingly parallel jobs.…”
Section: Introductionmentioning
confidence: 99%
“…This paradigm can solve those disadvantages with customizable virtual machines (VMs) that decouple the application execution from the underlying hardware and are dynamically provisioned and released [1]. Because of that, depending on the resource usage and the cost model, it might be convenient to deploy a virtual cluster instead of a physical one, as we concluded in a previous work [2]. Virtual clusters in the Cloud introduce profound benefits for many computational workloads, but specially for embarrassingly parallel jobs.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [2] we concluded that, in some cases, it is interesting to deploy a virtual cluster instead of a physical one. A virtual cluster in an IaaS provider is able to get a competitive performance per price rate, but also gets important benefits from the Cloud provider such as reducing the administration costs (both personnel costs and maintenance of equipments), avoiding hiring or buying the physical building to host the infrastructure, avoiding the upfront investments in hardware, cooling systems, etc.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main disadvantages of these platforms is the relatively large upfront investment together with the maintenance cost. For small and medium-sized research groups or organizations, the purchase of such an equipment might represent an important cost [58]. In addition, physical clusters cannot be easily enlarged or shrinked according to the dynamic requirements of the organization and they lack the ability to provide a tailored execution environment customized for each application to be executed, specially when incompatible libraries are required by different applications running on the same infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ability to transparently migrate running jobs to be executed on other physical resources is not a trivial task, which is an important feature for effective workload balancing. Another important limitation is the large upfront investment together with the maintenance cost of such computing equipment for small and medium-sized research groups or organizations [58].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation